Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd006732.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving the adoption of shared decision making by healthcare professionals

Abstract: The results of this Cochrane review do not allow us to draw firm conclusions about the most effective types of intervention for increasing healthcare professionals' adoption of SDM. Healthcare professional training may be important, as may the implementation of patient-mediated interventions such as decision aids. Given the paucity of evidence, however, those motivated by the ethical impetus to increase SDM in clinical practice will need to weigh the costs and potential benefits of interventions. Subsequent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
370
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 517 publications
(380 citation statements)
references
References 78 publications
8
370
0
2
Order By: Relevance
“…Training to enhance SDM skill in clinicians may be effective [22]; however, there is paucity of practical guidance with respect to accomplishing SDM practice and evidence shows that without practical interventions, most clinicians do not consistently implement it [14]. Clinicians may wish to audio-record consultations with patients' permission and score these, using the OPTION scale which would enable the prevalence of SDM to be measured as a self-directed learning or professional development activity.…”
Section: Discussionmentioning
confidence: 99%
“…Training to enhance SDM skill in clinicians may be effective [22]; however, there is paucity of practical guidance with respect to accomplishing SDM practice and evidence shows that without practical interventions, most clinicians do not consistently implement it [14]. Clinicians may wish to audio-record consultations with patients' permission and score these, using the OPTION scale which would enable the prevalence of SDM to be measured as a self-directed learning or professional development activity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support these objections is slim. Although consultation length varies depending on the context, no-one has yet proved that SDM systematically takes longer [37][38][39]. Models for interprofessional SDM have been developed and are being tested [40,41].…”
Section: Evidence Of Risks and Benefitsmentioning
confidence: 99%
“…Studies investigating the implementation of SDM interventions in somatic care have primarily taken place in the U.S.A. and the UK (Elwyn et al, 2012; Kashaf, McGill, & Berger, 2017; Légaré et al, 2010; Woodhouse et al, 2017). While few in number, implementation studies on SDM interventions in Sweden have suggested the importance of expanding the decision-making process beyond single encounters (Hultberg & Rudebeck, 2017) and beyond simply educating the patient in self-care (Herlitz, Munthe, Törner, & Forsander, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…SDM has only been implemented to a limited extent in Sweden and other Scandinavian countries (Légaré et al, 2014), despite the fact that SDM is one of the interventions recommended by the National Board of Health and Welfare in the Swedish Guidelines for Psychosocial Interventions for Schizophrenia or Schizophrenia-type conditions (2011/2017). While these recommendations are primarily based on evidence from Anglo-Saxon practice, the development and dissemination of new methods for psychosocial support have rapidly changed the field of community mental health in Sweden.…”
Section: Introductionmentioning
confidence: 99%